Mi hermana vive sobre la repisa de la chimenea - Pitcher, Annabel; Diez, Lola; Pitcher, Annabel (Madrid : Ediciones Siruela, 2011)
With his family still grieving over his sister's death in a terrorist bombing seven years earlier, twelve-year-old Jamie is far more interested in his cat, Roger, his birthday Spiderman T-shirt, and keeping his new Muslim friend Sunya a secret from his father.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Sisters -- Fiction; Bereavement -- Fiction; Talent shows -- Fiction; Grief -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Bombings -- Juvenile fiction; Twin sisters -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Children and death -- Juvenile fiction; Cremation -- Juvenile fiction; England -- Juvenile fiction; Electronic books